2012
DOI: 10.1089/ped.2011.0118
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Asthma Quick Relief Medication in Five Alabama School Systems

Abstract: Objectives: This paper documents individual asthma action plan presence and quick relief medication (albuterol) availability for elementary students enrolled in five Alabama school systems. Patients and Methods: Data were obtained during baseline data collection (fall 2005) of a school-based supervised asthma medication trial. All students attended 1 of 36 participating elementary schools across five school systems in Jefferson County, Alabama. In addition, they had to have physician-diagnosed asthma requiring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…They suggest that too few children have immediate access to rescue inhalers in school, especially if their families have low incomes, a finding similar to Gerald et al 15 Thus, the methods employed in this study provide a practical, relatively inexpensive way to determine the relative rates of childhood asthma at the local level in hundreds of schools. Identifying schools and the communities they serve that are at greatest risk is useful to public health departments and health care providers in many ways.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…They suggest that too few children have immediate access to rescue inhalers in school, especially if their families have low incomes, a finding similar to Gerald et al 15 Thus, the methods employed in this study provide a practical, relatively inexpensive way to determine the relative rates of childhood asthma at the local level in hundreds of schools. Identifying schools and the communities they serve that are at greatest risk is useful to public health departments and health care providers in many ways.…”
Section: Discussionsupporting
confidence: 75%
“…investigated the extent to which schools had a policy regarding the requirement for asthma action plans; Marshik et al, 14 who determined the extent to which children had access to their asthma medications during school hours; and Gerald et al, 15 who investigated the existence and completeness of individual asthma action plans on file and the availability of asthma medications in the school. All the investigators concluded that more effort should be devoted to managing the childrens' asthma in school.…”
Section: Borowsky Little and Catalettomentioning
confidence: 99%
“…11,12 A recent study involving five Alabama school districts observed that not one student with physician-confirmed asthma had a complete school asthma care plan/action plan on file at the school. 11,12 A recent study involving five Alabama school districts observed that not one student with physician-confirmed asthma had a complete school asthma care plan/action plan on file at the school.…”
Section: Why Center On Schools?mentioning
confidence: 99%
“…3 However, underreporting, a lack of asthma management plans, 4 and limited access to reliever medications complicate school-based asthma management. [5][6][7] The rate of asthma-related pediatric emergency department visits in Illinois in 2014 was 92 per 10 000, 8 which was much greater than the Healthy People 2020 goal of 49.6 per 10 000. 9 For non-Hispanic African American children, this figure was 265 per 10 000, which is 5.5 times higher than for non-Hispanic white children.…”
mentioning
confidence: 96%
“…limited access to care, forgetting their inhaler, or possessing one that is empty and/or expired complicate management. 14 Access to albuterol in schools may be as low as 14%, 5 and in Chicago Public Schools, only 25% of those with asthma had an action plan on file. 4 Stock asthma rescue medication policies aim to address these barriers by authorizing schools to maintain unassigned albuterol for administration to students with asthma symptoms by trained staff members.…”
mentioning
confidence: 99%